Low Amplified Spontaneous Emission and Lasing Thresholds from Hybrids of Fluorenes and Vinylphenylcarbazole. Issue 20 (26th August 2020) - Shukla, Atul; Mai, Van T. N.; Senevirathne, A. M. Chathuranganie; Allison, Ilene; McGregor, Sarah K. M.; Lepage, Romain J.; Wood, Michael; Matsushima, Toshinori; Moore, Evan G.; Krenske, Elizabeth H.; Sandanayaka, Atula S. D.; Adachi, Chihaya; et al.
Abstract: Organic semiconductor dyes have attracted high interest as laser gain media owing to their judicious features of solution processability, lightweight, high mechanical flexibility, high wavelength‐tunability, and low‐cost manufacture. In this work, fluorene‐carbazolylstyryl hybrids are reported, SFCz and BSTFCz, as new solution processable organic semiconductor laser dyes to show high molar extinction coefficients (up to 1.98 × 10 5 dm 3 mol −1 cm −1 ), high photoluminescence quantum yields (up to 81 ± 4%), high radiative decay constants (up to 1.24 × 10 9 s −1 ), and low film amplified spontaneous emission thresholds (down to 0.70 µJ cm −2 ). By using mixed‐order distributed feedback laser structures, extremely low lasing threshold of 0.5 µJ cm −2 is achieved. To elucidate their electroluminescent properties, simple solution‐processed organic light‐emitting diodes based on the new materials are fabricated to show good external quantum efficiencies (2%) and high brightness (≈2800 cd m −2 ). The results indicate the ease in material synthesis and fabrication enabling solution‐processed low‐threshold lasing toward future injection laser. Abstract : Extremely low amplified spontaneous emission and lasing thresholds are obtained from hybrids of fluorenes and vinylphenylcarbazole, the state‐of‐the‐art light amplification properties are attributed to high radiative rates (≈10 9 s −1 ), high photoluminescence quantum yields (≈80%), and low excited‐state absorption losses. Solution‐processed organic light‐emitting diodes fabricated using these materials as the emitters show efficient electroluminescence with low external quantum efficiency roll‐off.